Clinical Oral Surgery Program course guide - Concel, Luke Ivan F.
The Clinical Oral Surgery Program offers comprehensive undergraduate training for the Doctor of Dental Medicine. The program starts in the students' 5th year in the program. The clinicians are given a certain number of cases for each clinic level with the hope that they maximize their exposure and learning. The program includes four processes or cycles: the patient assessment, the initial process in which clinicians can evaluate different patients regardless of the patient's needs. After that, patients indicated for extraction will be further evaluated and prepared for the procedure. At this point, clinicians are tasked to create a specific treatment plan tailored to the patient. The next step of the process is pain management, in which clinicians need to administer local anesthesia. Techniques will vary depending on the case presented. And the fourth is Dentoalveolar surgery; this process is where the actual extraction of the tooth happens. This is the time that our skills can improve because a lot of principles are applied here. The oral surgery processes took inspiration from Kolb's experiential learning theory and learning styles, which focuses on the learner's personal development and perspective. Clinical instructors should investigate critical areas specified in this course guide with the sample Assessment tool and rubric. To help clinicians and clinical instructors, the section guidelines are also included in the paper.